Parallel Implementation of Elliptic Curve Method for Integer Factorization Using Message-Passing Interface (MPI) - Wolski, E.; S. Filho, Joel G.; Dantas, M. A. R. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2001: Anais do XIII Symposium on Computer Architecture and High Performance Computing, 2001)
One of the most prominent systems for securing eletronic information, known as RSA (Rivest-Shamir-Adleman) [RIV78], relies upon the fact that it is computationally difficult to factor a large integer into its component prime integers. lf an efficient algorithm is developed that can factor any arbitrarily large integer in a reasonable amount of time, the security value of the RSA system would be nullified. In this paper we present the Elliptic Curve Method for integer factorization and results of its parallel implementation using Message-Passing Interface (MPI).